1996
DOI: 10.1172/jci119022
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide contributes to estrogen-induced vasodilation of the ovine uterine circulation.

Abstract: Estradiol-17 ␤ (E 2 ␤ ), a potent vasodilator, has its greatest effects on the uterine vasculature, blood flow (UBF) increasing Ն 10-fold. The mechanism(s) responsible for E 2 ␤ -induced vasodilation is unclear. We determined if nitric oxide (NO)-induced increases in cGMP modulate estrogen-induced increases in UBF, and if cyclooxygenase inhibition modifies E 2 ␤ responses. Nonpregnant ( n ϭ 15) and pregnant ( n ϭ 8) ewes had flow probes implanted on main uterine arteries and catheters in branches of the uterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
193
1
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(219 citation statements)
references
References 57 publications
12
193
1
5
Order By: Relevance
“…in the in vivo uterine circulation (Van Buren et al 1992, Rosenfeld et al 1996. Our data do not provide a clear mechanistic explanation for the L-NAME insensitivity of the uterine arterial relaxing responses to E 4 .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…in the in vivo uterine circulation (Van Buren et al 1992, Rosenfeld et al 1996. Our data do not provide a clear mechanistic explanation for the L-NAME insensitivity of the uterine arterial relaxing responses to E 4 .…”
Section: Discussioncontrasting
confidence: 59%
“…Similarly, administration of E 2 to ovariectomized ewes results in a rapid uterine vasodilation leading to a rise in uterine blood flow within 30-45 min (Killam et al 1973). This rise in uterine blood flow is partially mediated via the release of nitric oxide (NO) and resultant increases in cGMP secretion, as shown by local infusion of the NO synthase blocker N u -nitro-L-arginine methyl ester (L-NAME; Van Buren et al 1992, Rosenfeld et al 1996. The dilating effect of E 2 on ovine uterine arteries is ER dependent, as shown by local infusion of the nonselective ER blocker ICI 182 780 in nonpregnant ewes (Magness et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for increased NO-dependent activity in the umbilical vascular bed of the compromised fetus during subsequent acute hypoxemia may be due to a number of factors, including greater generation of NO, increased expression of NO synthase in fetoplacental tissue, 15 increased sensitivity of the placental vascular tissue to NO, and/or greater synthesis of vasoactive factors that reduce umbilical-placental tone through NO-dependent mechanisms. Candidate factors include adenosine, 16 estrogen, 17 and/or adrenomedullin. 18,19 In addition, we have previously shown that fetuses preexposed to umbilical cord compression have elevated basal plasma concentrations of cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…생리주기의 난포기와 임신 중에는 혈 중 난포호르몬의 농도가 증가하고 이와 동반하여 자궁혈류가 상승하게 되고, 난소의 제거 후에 난포호르몬 보충치료를 받는 경우에도 자궁혈 류가 증가하게 되는 것으로 보아 난포호르몬이 자궁혈류의 증가에 중추 적인 역할을 하는 것으로 증명되고 있다 [12,13]. 난포호르몬이나 임신과 관련되어 자궁혈류가 증가하는 것은 주로 내피세포 산화질소 합성효소 (endothelial nitric oxide synthase, eNOS) 단백질 발현과 활성도가 증가 되어 혈관확장 물질인 산화질소(nitric oxide, NO)가 많이 생산되기 때문 인 것으로 알려져 있다 [14][15][16][17][18]. 난포호르몬에 의한 혈관이완은 생식계 동맥뿐 아니라 비생식계동맥 등 동맥혈관 전체에 대한 일반적인 효과이 며, 이는 산화질소 이외에도 prostacyclin과 같은 혈관 확장물질의 생성 의 증가와 endothelin-1과 thromboxane과 같은 혈관 수축물질의 억제 를 통한 이중 효과에 의한 것으로 추정된다 [19].…”
unclassified
“…난포호르몬에 의한 혈관이완은 생식계 동맥뿐 아니라 비생식계동맥 등 동맥혈관 전체에 대한 일반적인 효과이 며, 이는 산화질소 이외에도 prostacyclin과 같은 혈관 확장물질의 생성 의 증가와 endothelin-1과 thromboxane과 같은 혈관 수축물질의 억제 를 통한 이중 효과에 의한 것으로 추정된다 [19]. 혈관내피 세포와 산화질소-의존성 기전이 난포호르몬과 임신에 의 한 자궁혈류 증가에 중요한 역할을 하지만, 특이적인 내피세포 산화질 소 합성효소 억제제를 이용하여 내피세포에서 산화질소 작용을 차단하 더라도 난포호르몬이 유발한 자궁혈류 증가는 부분적(-65%)으로만 억 제되고 [14,15], 내피를 제거한 혈관에서도 난포호르몬에 의한 혈관확장 작용이 여전히 존재하는 것이 증명되었다 [18][19][20]. 그러므로 난포호르 몬에 의한 자궁동맥의 혈관확장 작용에는 혈관내피 세포/산화질소-의 존성 기전뿐 아니라 -비의존성 기전도 존재한다는 것을 추측할 수 있다 [18][19][20][21] …”
unclassified